2020
DOI: 10.1093/pcmedi/pbaa038
|View full text |Cite
|
Sign up to set email alerts
|

Making radiation therapy more effective in the era of precision medicine

Abstract: Cancer has become a leading cause of death and constitutes an enormous burden worldwide. Radiation is a principle treatment modality used alone or in combination with other forms of therapy, with 50%–70% of cancer patients receiving radiotherapy at some point during their illness. It has been suggested that traditional radiotherapy (daily fractions of approximately 1.8–2 Gy over several weeks) might select for radioresistant tumor cell sub-populations, which, if not sterilized, give rise to local treatment fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 134 publications
0
4
0
Order By: Relevance
“…Hence, hyper-fractionation of RT can maximize the probability of resistance in normal cells by making cancer cells sensitive. Molecular mechanisms such as decreased ROS can lead to DNA damage, which increases the DNA repair capacity and thus leads to autophagy or other self-renewal mechanisms contributing to cellular resistance [63]. Hence, challenges remain to minimize or eradicate the resistant tumor sub-population more than the sensitive tumor sub-population.…”
Section: Riar Studies In the Relevant Clinical Scenariomentioning
confidence: 99%
“…Hence, hyper-fractionation of RT can maximize the probability of resistance in normal cells by making cancer cells sensitive. Molecular mechanisms such as decreased ROS can lead to DNA damage, which increases the DNA repair capacity and thus leads to autophagy or other self-renewal mechanisms contributing to cellular resistance [63]. Hence, challenges remain to minimize or eradicate the resistant tumor sub-population more than the sensitive tumor sub-population.…”
Section: Riar Studies In the Relevant Clinical Scenariomentioning
confidence: 99%
“…The failure of NormRT is associated with tumor heterogeneity and radiation-stimulated radio resistance. Accelerated dose per fraction protocols may open a therapeutic window for radiation dose optimization in NSCLC, since a small dose per fraction RT may select for radioresistant tumor cells, while hypofractionation may sensitize tumor cells to subsequent irradiation ( 8 ). Therefore, stereotactic ablative radiotherapy (SBRT) for small tumors with a few high dose fractions or moderate hypofractionated radiotherapy (HypoRT) for patients with locally advanced NSCLC, have recently gained clinical importance as alternative RT treatment ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the mastectomy rates remaining between 30% and 40% (3). Post-mastectomy radiotherapy (PMRT) is associated with a better local control and overall survival benefit in patients with unfavorable pathologic features (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%